Smart bidding modern antique eShop - Soon, Yu Siang (2023)
Modern antique system is a platform that allow the consumer to purchase antique online without going to the physical store. As the digitalization, there were many businesses transforming from the physical to the online. So does the antique shop, as this Modern antique shop that we are going to develop, will be one of a complete e-shop that will convenient the consumer by applying different kind of feature and algorithm in the proposed system. The main goal of this project is to create a fully functional web application of a Modern antique e-shop.